Sunproofed study protocol: A mixed-methods scoping study of sun safety policies in primary schools in Wales. - Julie Peconi; Claire O'Neill; Greg Fegan; Kirsty Lanyon; Timothy Driscoll; Ashley Akbari; Alan Watkins; Rachel Abbott (PLoS ONE)
Background Skin cancer, including melanoma and non-melanoma (keratinocyte), is increasing in incidence in the UK. Accounting for half of all cancers in England and Wales, the disease significantly impacts overstretched dermatology services. Research suggests that 86% of melanoma is preventable with modified sun exposure. Educating children about sun safety in schools can help prevent skin cancer and is recommended by major health organisations. In England, teaching sun safety in primary schools is compulsory, while in Wales this is left to school discretion. Aims Understand how primary schools in Wales are responding to growing skin cancer rates and explore the effectiveness of sun safety policies in schools on knowledge and behaviour. Methods Sunproofed is a mixed-methods scoping study comprising 5 work packages (WP) using survey and routine electronic health record (EHR) data supplemented by qualitative case studies. Objective(s) are to: WP1: Discover if primary schools in Wales have sun safety policies; policy characteristics; determine factors that may influence their presence and identify areas where schools need support. WP2: Determine what EHR data is available regarding the incidence of sunburn in primary school children and the feasibility of using this data to evaluate the impact of sun safety policies. WP3: Understand the impact of sun safety policies on sun-safe knowledge and behaviour amongst children, parents, teachers, and school management; identify barriers and facilitators to schools implementing sun safety policies. WP4: Co-produce guidance regarding sun safety policies and best methods for implementation in schools. WP5: Disseminate guidance and findings widely to ensure impact and uptake. Discussion Skin cancer rates are increasing in the UK, straining limited resources. Sunproofed has the potential to inform the development of future prevention activities, both in Wales and beyond. This could reduce the number of skin cancer cases in the future and keep people healthier for longer.